Computer simulation of the rough lipopolysaccharide membrane of Pseudomonas aeruginosa. - Lins, R D (2001)
Lipopolysaccharides (LPSs) form the major constituent of the outer membrane of Gram-negative bacteria, and are believed to play a key role in processes that govern microbial metal binding, microbial adsorption to mineral surfaces, and microbe-mediated oxidation/reduction reactions at the bacterial exterior surface. A computational modeling capability is being developed for the study of geochemical reactions at the outer bacterial envelope of Gram-negative bacteria. A molecular model for the rough LPS of Pseudomonas aeruginosa has been designed based on experimentally determined structural information. An electrostatic model was developed based on Hartree-Fock SCF calculations of the complete LPS molecule to obtain partial atomic charges. The exterior of the bacterial membrane was assembled by replication of a single LPS molecule and a single phospholipid molecule. Molecular dynamics simulations of the rough LPS membrane of P. aeruginosa were carried out and trajectories were analyzed for the energetic and structural factors that determine the role of LPS in processes at the cell surface.